Physical Activity, Self-Efficacy and Self-Esteem in Breast Cancer Survivors: A Panel Model - Awick, Elizabeth A. (Psychooncology, 2016)
PURPOSE: Physical activity (PA) has been consistently associated with improved self-esteem in breast cancer survivors. However, this relationship is poorly understood. The purpose of this study was to examine whether changes in PA and self-efficacy influenced changes in self-esteem in breast cancer survivors across six-months. Increases in PA were hypothesized to result in increases in self-efficacy which were hypothesized to influence increases in physical self-worth and global self-esteem. METHODS: Breast cancer survivors (n=370; M(age) = 56.04) wore accelerometers to measure PA and completed measures of self-efficacy (e.g., exercise and barriers self-efficacy), physical self-worth, and global self-esteem at baseline and 6 months. RESULTS: The hypothesized model provided a good fit to the data (χ(2) =67.56, df = 26, p <.001; CFI = .98; SRMR = .05). Women with higher activity at baseline reported significantly higher levels of barrier (β = .29) and exercise (β = .23) self-efficacy. In turn, more efficacious women reported significantly higher physical self-worth (β = .26, .16). Finally, higher physical self-worth was significantly associated with greater global self-esteem (β = .47). Relationships were similar among changes in model constructs over 6 months. After controlling for covariates, the hypothesized model provided an excellent fit to the data (χ(2) =59.93, df = 33, p =.003; CFI = .99; SRMR = .03). CONCLUSION: Our findings provide support for the role played by PA and self-efficacy in positive self-esteem, a key component of well-being. Highlighting successful PA mastery experiences is likely to enhance self-efficacy and improve self-esteem in this population.